2002
DOI: 10.1177/000348940211100304
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epstein-Barr Virus and Nasopharyngeal Carcinoma in Caucasian Patients

Abstract: We evaluated the association of nasopharyngeal carcinoma (NPC) and Epstein-Barr virus (EBV) in Spanish patients, and studied the expression of EBV products (latent membrane protein-1 [LMP-1] and ZEBRA proteins) by NPC cells and its possible prognostic value. In situ hybridization (ISH) for EBV-encoded nonpolyadenylated RNAs (EBERs) and immunohistochemical expression of LMP-1 and ZEBRA proteins by immunohistochemistry were examined in formalin-fixed, paraffin-embedded NPC specimens from 30 patients, and a survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…We also found that all three histological types of NPC were associated with the presence of EBV. Our results are consistent with previous reports which suggest that NPC in the Mediterranean basin resembles the Asian type and is strictly associated with the EBV infection [2,13,40].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that all three histological types of NPC were associated with the presence of EBV. Our results are consistent with previous reports which suggest that NPC in the Mediterranean basin resembles the Asian type and is strictly associated with the EBV infection [2,13,40].…”
Section: Discussionsupporting
confidence: 93%
“…The Spanish trial studied 30 specimens from patients with NPC, 29 of which were positive by EBER ISH, but only 13 were positive by LMP-1 IHC. 15 The Italian study found that 16 of 24 samples of non-keratinising (types 2 and 3) NPC were positive by EBER ISH. 16 The results of our present study in an Israeli population, in which 40 of 45 patients were positive by EBER ISH, are similar to these last two studies, although only six of our 45 patients were positive for LMP-1 IHC.…”
Section: Discussionmentioning
confidence: 98%
“…In 1973, presence of EBV genomes was demonstrated in epithelial NPC cells [18] and EBV-related antigens were detected in the tumor cells of all NPC patients [26]. Subsequently, the expression of the viral genome in non-keratinising NPC has been studied extensively in areas with NPC epidemic [14], [16], [27] and major types of viral expression proteins have been found, e.g., EBNA1 [28][30], LMP1 [15], [31]–[34] and LMP2A [31]. Moreover, in case-control studies, NPC cases showed significantly higher antibody titers to EBV antigens than controls in several retrospective studies [11], [19], [35][38].…”
Section: Introductionmentioning
confidence: 99%